Implementasi PhET Interactive Simulation dalam Meningkatkan Pemahaman Konsep Persamaan Garis Lurus Mahasiswa Calon Guru Sekolah Dasar - Muhammad Erfan; Mohammad Archi Maulyda (STKIP Andi Matappa Pangkep, 2022)
The concept of a linear equation is an initial concept that must be mastered by prospective elementary school teachers. This study aims to improve the understanding of the concept of linear equations for elementary school teacher candidates by implementing PhET Interactive Simulation. This research is a quasi-experimental study with a pre-test-post-test control group design. The sample in this study was class 2F as the experimental class, namely the class that learned the concept of linear equations using PhET Interactive Simulation and class 2H as the control class, namely the class that learned the concept of straight-line equations conventionally (lectures or online meetings). Data on the concept understanding of linear equations were obtained by test and analyzed by independent sample t-test and normalized gain test. The results showed that the experimental class showed a significant increase in understanding the concept of linear equations compared to the control class. The average value of students' conceptual understanding on linear equations in the experimental class is higher than the post-test average in the control class, so PhET Interactive Simulation is effective in improving students' understanding of straight-line equations concepts.